Numerical modelling of full-scale subsea lander Amalia with in situ conditions. Issue 4 (1st December 2020) - Assis Gonçalves, Filipe; Onofre Gomes, Miguel; Mathias, Nuno; Morais, Tiago; Ferradosa, Tiago
Abstract : The Amalia lander is a modular gravity-based structure capable of executing different tasks in subsea conditions such as monitoring, surveillance and docking autonomous underwater vehicles, and could work as a platform for validating coatings, damage at foundations and scour protections and integrity of new materials, among other applications. This lander has a unique complex geometry and is made of the eco-friendly material polyoxymethylene, a high-performance thermoplastic of low cost, low density and high stiffness. This paper elaborates on the latest design developments of Amalia, including in situ material characterisation and numerical modelling activities, which focus on fulfilling the rising needs of the blue economy in the subsea engineering field. Material characterisation included tensile and Charpy impact experimental tests. The experimental curve was used to improve the numerical models (Ansys software). Full-scale data, obtained at Berlenga Grande Island, were used to compile design information on loads and boundary conditions in order to set numerical and experimental trials used to study Amalia's structural reliability. The Amalia lander was studied and its design was upgraded, the details of which are presented here. Further research showed that both the interface between the rod and the ballast weight and the bearing connection between the cage and the sphere fork can be improved.